THE ORGANIZATION OF EDUCATION ON THE BASIS OF MODERN EDUCATION IS A GUARANTEE OF IMPROVING THE QUALITY OF EDUCATION - Botirova M; Mirxayitova N. S (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the recent past, the terms "Innovative Education", "Innovative Activity" and "Innovative Processes" were rarely observed in the pedagogical literature of the republic. At the heart of the word innovative education is a complex activity, such as the organization of innovation, the acquisition of innovation, the use of innovation, the demonstration of innovation.